Computer-aided design of variable frequency UHF oscillators using bipolar transistors - Araneta, Jose C. (1973)
A computer program to be used as a tool for designing variable frequency UHF oscillators, utilizing a bipolar transistor as the active device and a co-axial cavity resonator as the frequency-determining element, was developed. It included biasing network design and cavity resonator design. A separate program for designing the heat sink of the bipolar transistor was also developed. Transient analysis of the oscillator network as an approach to the simulation of the whole system was originally included. The inhenrently slow-speed of computation of the numerical integration technique used made simulation an impractical component of the whole program. However, transient analysis using implicit numerical integration is recommended for inclusion to give the designer a more detailed information to work with. An example illustrating the usefullness of the program is given.